ANALISIS DAMPAK PROGRAM PEMBERDAYAAN MASYARAKAT (COMMUNITY DEVELOPMENT) PT. SUMBAWA TIMUR MINING (STM) TERHADAP KEHIDUPAN SOSIAL–EKONOMI MASYARAKAT - . Ramadhoan (Jurnal Ekonomi Pembangunan, 2015)
The purpose of this study was to analyze the impact of community empowerment programs conducted by PT. STM to the social and economic life of society, both directly and indirectly. The method used is a qualitative and quantitative data collection techniques using observation method, the method of documentation, interview and questionnaire. Technical analysis of the data used in the method of qualitative research is data reduction, data display and conclusion; Technical analysis of the data that is used mainly on quantitative methods are counting frequency. The results showed that in terms of direct benefits, the vast majority of corporate social responsibility is embodied in the form of community empowerment program very useful. However, if the terms of the indirect benefits of community empowerment programs implemented by the company is still less perceived benefits. This can be understood as the activities carried out by PT. East Sumbawa Mining (STM) are still at the exploratory stage and given the share of allocation of funds spent on community empowerment program is still relatively small compared to the total allocation of development funds in the District of Hu'u. Social impact is more felt by the people than the economic impact. It is due to that ComDev in economics is relatively small when compared to the social sector, both in terms of budget as well as routine and sustainability programs.